Mixture × Genotype Effects in Cereal/Legume Intercropping - Demie, Dereje T.; Döring, Thomas F.; Finckh, Maria R.; van der Werf, Wopke; Enjalbert, Jérôme; Seidel, Sabine J. (Frontiers in Plant Science, 2022)
Cropping system diversification through annual intercropping provides a pathway for agricultural production with reduced inputs of fertilizer and pesticides. While several studies have shown that intercrop performance depends on the genotypes used, the available evidence has not been synthesized in an overarching analysis. Here we review the effects of genotypes in cereal/legume intercropping systems, showing how genotype choice affects mixture performance. Further, we discuss the mechanisms underlying the interactions between genotype and cropping system (i.e., sole cropping vs. intercropping). Data from 69 articles fulfilling inclusion criteria were analyzed, out of which 35 papers reported Land Equivalent Ratio (LER), yielding 262 LER data points to be extracted. The mean and median LER were 1.26 and 1.24, respectively. The extracted genotype × cropping system interaction effects on yield were reported in 71% out of 69 publications. Out of this, genotype × cropping system interaction effects were significant in 75%, of the studies; while 25% reported non-significant interactions. The remaining studies did not report the effects of genotype × cropping system. Phenological and morphological traits such as differences in days to maturity, plant height, or growth habit explained variations in the performance of mixtures with different genotypes. However, the relevant genotype traits were not described sufficiently in most of the studies to allow for a detailed analysis. A tendency towards higher intercropping performance with short cereal genotypes was observed. The results show the importance of genotype selection for better complementarity in cereal/legume intercropping. This study highlights the hitherto unrevealed aspects of genotype evaluation for intercropping systems that needs to be tackled. Future research on genotype effects in intercropping should consider phenology, root growth, and soil nutrient and water acquisition timing, as well as the effects of weeds and diseases, to improve our understanding of how genotype combination and breeding may help to optimize intercropping systems.